The cognitive, behavioral and social prospectives of organizational learning through information system - Turi, Jamshid Ali; Sorooshian, Shahryar; Fatimah, Mahmud; Javed, Yasir (University of Malaya, 2018)
This study set out to examine, cognitive, behavioural and social factors of learning theoretically and contemporarily with the moderating role of information system in the learning organization. Cognitive, social and behavioural theories were discussed and the use information system for organizational learning effectiveness was studied. Data was collected from the lecturers’ employees working in the universities of Islamabad and Rawalpindi in Pakistan, using convenient sampling method and survey technique using questionnaire. Total of 113 Universities’ lecturers from different faculties of the universities participated in the survey. Data was analysed with SPSS. The findings indicate that cognitive, social and behavioural organizational factors have significant impacts on organizational learning effectiveness with the moderating support of information system. The study recommends that for the holistic organizational learning development, all cognitive, social and behavioural aspects and factors needs to be addressed and developed.